Reproductive strategies of two color morphs of Paeonia delavayi - Duan, Lijun; Wang, Juan; Li, Haiqing; Li, Jin; Tong, Haizhen; Du, Chun; Zhang, Huaibi (Frontiers in Plant Science, 2025)
The diversity in floral coloration results from a complex reproductive system, which has evolved in response to multiple pollinators and is intricately linked to the development of pollination mechanisms. To investigate how floral trait variations influence reproduction in Paeonia delavayi, we conducted pollination experiments, observed insect visitation, measured floral traits, estimated petal and anther colors as perceived by pollinators and analyzed floral scent for two floral morphs (red and yellow) at two distinct sites. P. delavayi depended on insect pollinators for seed production. Multiple comparisons revealed that seed yields and seed sets under natural pollination were significantly higher than those under artificial pollination (homogamy and geitonogamy) and anemophilous pollination. However, there was no significant difference in seed yields(LWS, p = 0.487; XGLL, p = 0.702) and seed set (LWS, p = 0.077; XGLL, p = 0.251) between two floral morphs under natural pollination. Both morphs shared common pollinators, primarily honeybees, bumblebees, and syrphid flies. Major pollinators visited the yellow morph more frequently than the red morph, although there was no significant difference in the duration time of visits between the two morphs. Studies utilizing insect vision models, based on color reflection spectra, revealed that major pollinators could distinguish differences in petal and anther colors between the two morphs. However, there is variation in how pollinators perceive their flower colors. On the one hand, the yellow morphs contrast against the leaves background, enhancing their visual attractiveness to bees and flies. On the other hand, the red-flowered morph compensates for its visual disadvantage through olfactory cues, ensuring successful reproduction despite lower visual attractiveness. This study highlights the intricate interplay between visual and olfactory signals in plant-pollinator interactions, emphasizing their combined influence on reproductive outcomes.